(untitled) - Latimer, Kenneth S. (Ames, Iowa, 2003)
Duncan and Prasse's Veterinary Laboratory Medicine provides the reader with an excellent overview of veterinary clinical pathology. The new edition retains its elegantly simple outline format and section organization (physiology, evaluation disorders, disorders, and appropriate clinical cases). This enables readers to quickly identify key words, ideas and information in the text. Each chapter is followed by a current reference list, primarily from refereed professional journals
Keywords: Veterinary clinical pathology,Chẩn đoán bệnh thú y